2022
DOI: 10.3390/healthcare10091639
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation-Based Clinical Nursing Education Framework for a Low-Resource Setting: A Multimethod Study

Abstract: Simulation-based clinical education is a useful strategy for teaching, learning, and assessing clinical competence in health professions education. However, the use of simulation-based clinical nursing education (SBCNE) in low-resource settings such as Ghana has been hampered by the lack of a context-specific framework to guide its design, implementation, and evaluation. This study sought to develop a context-specific framework to guide the design, implementation, and evaluation of SBCNE in a low-resource sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…This approach uses different research methods, such as literature review, interviews, and focus groups, in a specific sequence to complement each other’s results and build a more comprehensive understanding of the phenomenon under study ( Subedi, 2016 ). This approach has been widely employed in prior studies to integrate scoping review data with qualitative data ( Jolivet et al, 2021 ; Qiu et al, 2021 ; Claessens et al, 2022 ; Salifu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This approach uses different research methods, such as literature review, interviews, and focus groups, in a specific sequence to complement each other’s results and build a more comprehensive understanding of the phenomenon under study ( Subedi, 2016 ). This approach has been widely employed in prior studies to integrate scoping review data with qualitative data ( Jolivet et al, 2021 ; Qiu et al, 2021 ; Claessens et al, 2022 ; Salifu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, by experiencing clinical situations through prior learning linkages, professional cardiopulmonary resuscitation performance would increase by participating in face-to-face simulation practice with con dence. As previous studies indicated, evaluation and feedback can be effectively derived when instructors and learners interact in both directions [39]. Therefore, to increase professional cardiopulmonary resuscitation performance, it is necessary to apply a case-based pre-learning simulation and this class simulation by applying a PARTNER model when constructing education and to apply a blended learning method considering cooperative learning that communicates in both directions in this class.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in Sub-Saharan Africa, different teaching methods have been applied to improve nursing student's clinical competence, critical thinking, decision making, problem solving and patient safety. Such methods include simulation based clinical learning (17),concept map (18) and evidence based practice (19).…”
Section: Introductionmentioning
confidence: 99%